Spaceflight revolution - Ashford, David, 1939- (Imperial College Press ; Distributed by World Scientific, 2002)
A revolution in spaceflight is likely soon, with the prospect of everyday access to orbit. Costly ballistic missiles used to launch vehicles will be replaced by "spaceplanes", using technology that already exists. In a few years' time, a prototype could be built, and with further detailed development, the design could approach airliner maturity, reducing the cost of sending people into space some one thousand times. Spaceplane development has, in effect, been suppressed by entrenched thinking and short-term vested interests. But the present monopoly of large government space agencies is becoming unsupportable, and the market that understands the very real opportunities for space travel will be reaching critical mass in the near future. This is an examination of these issues, showing why space tourism will one day become the single largest business in space, and how astronomy will be transformed by low-cost access making practicable instruments orders of magnitude larger than those today